Effects of Cognitive Strategy Interventions and Cognitive Moderators on Word Problem Solving in Children at Risk for Problem Solving Difficulties. Issue 4 (November 2013) - Swanson, H. Lee; Lussier, Cathy; Orosco, Michael
<x xml:space="preserve">Abstract</x> This study investigated the role of strategy instruction and cognitive abilities on word problem solving accuracy in children with math difficulties (MD). Elementary school children (N = 120) with and without MD were randomly assigned to 1 of 4 conditions: general‐heuristic (e.g., underline question sentence), visual‐schematic presentation (diagrams), general‐heuristic + visual‐schematic, and an untreated control. When compared to the control condition that included children with MD, an advantage at posttest was found for children with MD for the visual‐schematic‐alone condition on measures of problem solving and calculation accuracy, whereas all strategy conditions facilitated posttest performance in correctly identifying problem solving components. The results also suggested that strategy conditions drew upon different cognitive resources. The General‐heuristic condition drew primarily upon the executive component of working memory (WM), Visual‐schematic condition drew upon the visual component of WM and the combined strategies condition drew upon number processing skills.